Nephrology Fellowship Clinician-Performed Ultrasound Curriculum - Nathaniel Reisinger; Nova Panebianco (CINQUILL Medical Publishers Inc., 2022)
Fluid overload (FO) contributes significantly to the development of cardiovascular disease among patients with end-stage kidney disease (ESKD) on hemodialysis (HD), yet remains underappreciated due to limitations of the physical exam [1]. Lung ultrasound (US) is an established tool for quantification of FO [2]. Previous validation of quantitative lung US among nephrology attendings using a remote web-based lung ultrasound training has been demonstrated [3]. Interest in ultrasound education among nephrology fellows is high [4]. Clinician-performed ultrasound curricula for nephrology fellows have been described previously, however fellows' competency in quantitative lung US has not been described [5]. In the present study we aimed to assess the current level of knowledge among nephrology fellows as well as the efficacy of a brief training course in quantitative lung US.